2008
DOI: 10.1002/pmic.200800083
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of a PSF/p54nrb heterodimer as RNF43 oncoprotein‐interacting proteins

Abstract: RNF43 is an oncogenic RING finger protein overexpressed in colorectal cancer. To dissect its biological functions, we explored RNF43-interacting proteins by pull-down assay and MS. We identified a heterodimer, p54nrb and PSF, as RNF43's binding partners and confirmed their physical interaction in vivo by the co-immunoprecipitation experiment. Immunofluorescence analysis revealed that co-expression of PSF relocates RNF43 from the nuclear periphery to the nucleoplasm. Thus, proteomic identification of RNF43-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
2
11
1
Order By: Relevance
“…To investigate how NONO/PSF might facilitate global pri-miRNA processing, we performed UV CrossLinking ImmunoPrecipitation coupled with deep sequencing (CLIP-seq) to identify their direct RNA targets. Both anti-NONO and anti-PSF antibodies efficiently brought down the NONO/PSF heterodimer, as reported earlier 40 , 41 , each of which was crosslinked to RNA, as detected by 32 p-labeling with T4 polynucleotide kinase ( Fig. 3a ; Supplementary Fig.…”
Section: Resultssupporting
confidence: 82%
“…To investigate how NONO/PSF might facilitate global pri-miRNA processing, we performed UV CrossLinking ImmunoPrecipitation coupled with deep sequencing (CLIP-seq) to identify their direct RNA targets. Both anti-NONO and anti-PSF antibodies efficiently brought down the NONO/PSF heterodimer, as reported earlier 40 , 41 , each of which was crosslinked to RNA, as detected by 32 p-labeling with T4 polynucleotide kinase ( Fig. 3a ; Supplementary Fig.…”
Section: Resultssupporting
confidence: 82%
“…Thus co-expressing the same SFPQ protein used for Crystal 1 along with the dimerization domain of NONO results in formation of SFPQ-276–598/NONO-53–312 heterodimers. We note that the SFPQ/NONO heterodimer may in fact be more physiologically relevant than the SFPQ homodimer, as SFPQ was first discovered as a heterodimer with NONO ( 33 ) and many studies since have observed SFPQ and NONO colocalized and co-purified ( 12 , 34 ).…”
Section: Resultsmentioning
confidence: 90%
“…It has been shown to reside in the inner nuclear membrane, the nuclear periphery and nucleoplasm,10 the endoplasmic reticulum6 and on the surface cell membrane where it interacts with Frizzled 8. The presence of the signal peptide determines the distribution of RNF43 to the plasma membrane, while its lack results predominantly in the cytoplasmic dislocation 8…”
Section: Localisationmentioning
confidence: 99%